A Simple Method to Improve the Geoid from a Global Geopotential Model (or Coarse Geoid Estimation Using Only the Innermost Zone Contribution of Stokes's Formula) - Featherstone, Will (International Geoid Service, 2002)
This paper presents the results of curiosity-driven experiments to determine how well, if at all, only the innermost zone contribution of Stoke's formula can model the geoid for GPS height transformation. Terrestrial gravity and terrain data are used over Australia, and the results compared with GPS-derived ellipsoidal and Australian Height Datum heights. The results are largely as expected in that the innermost zone contribution to the total geoid height is small. While this approach does not improve upon a regional gravimetric geoid model, it does make a small improvement upon a global geopotential model. Therefore, in areas where regional gravity and terrain data are limited, some small improvements may be made to existing global geopotential models by calculating the innermost zone contribution from localised gravity and terrain data. This is an extraordinarily simple calculation. It may prove to be of value to those who do not have access to regional gravity data (i.e., due to restricted field access or confidentiality) or resources (i.e., personnel, software and high-powered computers) to compile a locally improved geoid model. Accordingly, the method can provide an interim geoid model until the issues of data availability and resources have been resolved to allow the compilation of a regional gravimetric geoid model.